Method for preparing high-entropy alloy through cascade electric exchange technology

Through class UMC Exchange Technology to introduce multiple cations in metal oxide particles, using (AG7O8) X super -structural material as a template to solve the problem of difficulty synthesizing multi -element nanoparticles in existing technology, realizing high -efficiency high -entropy alloys Hollow super -structural material.

CN119372734AActive Publication Date: 2025-01-28ZHEJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411897034.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

It is difficult to effectively synthesize nanoparticles composed of multiple elements, especially those containing elements with large chemical properties, and traditional methods have low yields and high equipment requirements.

Method used

Adopting grade UMC exchange technology, according to the sequence of the oxidation and reduction potential of different cations, up to 6 yang ions to metal oxide particles in turn, through the (AG7O8) X super -structural material as a template, and ion exchange with a variety of metal salt solutions for ion switching Reaction, prepare high -entropy alloy hollow super -structural materials.

Benefits of technology

A reasonable design and efficient preparation of multi -component metal oxides, increasing the complexity and yield of nanoparticles, reducing equipment requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372734A_ABST
    Figure CN119372734A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-entropy alloy by using a cascade electric exchange technology. According to the method, an (Ag7O8) X superstructure material is used as a template and is subjected to an ion exchange reaction with a plurality of metal salt solutions in sequence, the oxidation potential of metal cations in the metal salt solutions is lower than that of silver ions in the (Ag7O8) X superstructure material, the oxidation potential is gradually reduced according to the sequence of introduction of the (Ag7O8) X superstructure material, and the silver ions in the (Ag7O8) X superstructure material are gradually reduced according to the sequence of introduction of the (Ag7O8) X superstructure material. Through the continuous cascade electric exchange process, conversion of alloy components is achieved, and the multi-element high-entropy alloy is successfully synthesized. The prepared superstructure material contains Fe and Co, is endowed with magnetism, and can realize the driving of a magnetic control micro motor under the action of an external electric field. In addition, the Ag (Ni, Co, Fe) O2 alloy prepared by the method can be used as a water electrolysis catalyst, and shows good electro-catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical deposition and relates to a method for preparing a high entropy alloy by utilizing a cascade electrical exchange technology. Background Art

[0002] In recent years, the composition of nanoparticles plays a key role in determining their properties. In order to meet the demanding requirements in catalysis, optoelectronic devices, sensing and biomedical fields, it is often necessary to increase the compositional complexity of nanoparticles. There are currently a variety of methods to prepare nanoparticles composed of multiple materials, including templates, surface patterning, local deposition and nanoreactor technologies. However, these methods can only produce products in very low yields (microgram levels) and require specialized equipment. Solution methods can prepare large quantities of nanoparticles using benchtop chemical reagents and ordinary laboratory glassware. However, it is very challenging to directly synthesize nanoparticles composed of multiple elements using solution methods, especially those that need to include elements with large chemical properties. For example, it is difficult to make heterostructured nanoparticles composed of only two materials.

[0003] Schaak et al. introduced new cations into nanoparticles one by one through partial cation exchange reactions, thus forming extremely complex nanoparticles in composition and interface. Cation exchange reactions follow certain mobility, solvation energy and Lewis acid-base interactions, so the cation exchange process limits the versatility of composition design. Exploring new mechanisms driving the exchange between different cations is of great significance for the design of multi-component nanoparticles. Zinc displacement reactions usually occur between active metal nanoparticles and noble metal ions driven by redox potential differences, usually producing core, shell or hollow metal nanoparticles.

[0004] In 2013, Hyeon et al. first discovered Mn in xylene. 3 O 4 or Co 3 O 4 Nanocrystals (~ 20 nm) with Fe 2+ or Sn 2+ Electroexchange reactions between ions. Here, a cascade electroexchange method is developed to rationally incorporate cations into metal oxide microparticles in a sequential manner. Up to 6 cations are introduced into the microparticles (~ 10µm) in sequence according to their redox potential in aqueous solution at room temperature. Cations that are already at the highest valence can also be added by activating the microparticles with reducing or intermediate valence ions. The introduction of cations into the structure according to simple criteria based on the redox potential of the different cations opens up a path to the rational design and synthesis of multicomponent metal oxides. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a high entropy alloy by using cascade electrical exchange technology in view of the shortcomings of the prior art.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: As a first aspect, the present invention provides a method for preparing a high entropy alloy using a cascade electrical exchange technology, comprising the following steps: (Ag 7 O 8 )X superstructure material is used as a template to sequentially undergo ion exchange reactions with a variety of metal salt solutions; in each ion exchange reaction, the progress of the ion exchange reaction is detected by the open circuit voltage, and the reactants are separated before the value of the open circuit voltage stabilizes, thereby preparing a multi-component high entropy alloy hollow superstructure material; Wherein, the oxidation potential of the metal cations in the plurality of metal salt solutions is lower than that of the (Ag 7 O 8 )X superstructure material, and the oxidation potential of silver ions introduced by (Ag 7 O 8 )X superstructure materials in order, the oxidation potential gradually decreases; X anion is selected from NO 3 - , HSO 4 - , ClO 4 - , F - , BF 4 - One or more of .

[0007] Furthermore, the concentration of the metal salt solution is greater than 50 mmol / L.

[0008] Furthermore, the (Ag 7 O 8 The X superstructure material is prepared by the following method: a three-electrode system is used to contain silver ion compounds and H 3 BO 3 The deionized water solution is used as the electrolyte, and the Ag is deposited on the working electrode in a step-by-step voltage changing mode or multiple step-by-step voltage changing modes. 7 O 8 )X superstructure material; wherein the voltage of the electrodeposition is greater than or equal to 1.5 V, and the silver ion compound is AgNO 3 , Ag 2 SO 4 , AgClO 4 , AgF, AgBF 4 One or more of .

[0009] Furthermore, (Ag 7 O 8)X superstructure material as a template, and ion exchange reaction with various metal salt solutions in sequence, specifically: (Ag 7 O 8 )X superstructure material is a conductive electrode (as a positive electrode), a metal cation solution is used as an electrolyte (as a negative electrode), and a carbon rod is used as a counter electrode; high-valent silver ions gradually move from (Ag 7 O 8 )X superstructure material diffuses from the inside out, and metal cations gradually attach to (Ag 7 O 8 )X superstructure material surface, forming a growing AgYO 2 Shell (Y represents the metal element in the metal cation, such as Ni, Co, etc.), to obtain the second generation hollow metal oxide material AgYO 2 , orthorhombic Ag 7 O 8 Nitrate and triangular crystal AgYO 2 The crystallographic similarity of Ag 7 O 8 NO 3 ,AgYO 2 Lattice distortion between core and shell; the second generation of hollow metal oxide material AgYO 2 As a template, the above steps are repeated to react with metal cations with an oxidation potential lower than Y to obtain a multi-generation multi-component high entropy alloy hollow superstructure material.

[0010] Furthermore, it also includes: introducing the highest valence cation (Ag 7 O 8 )X superstructure material or nth generation multi-component high entropy alloy hollow superstructure material, specifically, placing an intermediate valence cation solution in a first container, inserting a carbon rod, placing the highest valence cation solution to be introduced in a second container, inserting (Ag 7 O 8 ) a gold electrode covered with an X superstructure material or an nth generation multi-component high entropy alloy hollow superstructure material, the gold electrode is connected to the carbon rod by a copper wire, the first container and the second container are connected by a liquid bridge, and the liquid bridge is provided with an ion exchange membrane, which only allows X anions to pass through; wherein the oxidation potential of the intermediate valence cation is higher than that of the highest valence cation.

[0011] As a second aspect, the present invention provides a multi-component hollow superstructure material prepared by the method described above.

[0012] As a third aspect, the present invention provides a use of the multi-component hollow superstructure material in preparing microcapsules, using Co 2+ and Fe 2+ The metal salt solution was used to prepare Ag(Co,Fe)O 2The magnetic superstructure material and the microcapsule are used for delivering drugs to target locations in the human body.

[0013] As a fourth aspect, the present invention provides a use of the multi-component hollow superstructure material in preparing a SERS substrate.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention opens up a path for the rational design of multi-component metal oxides by introducing cations into the structure according to simple criteria based on the redox potentials of different cations; rationally incorporating cations into metal oxide microparticles in a sequential manner; sequentially introducing up to six cations into the microparticles (~10 µm) according to the order of their redox potentials in aqueous solution at room temperature; cations that are already at the highest valence can also be added by activating the microparticles using reducing or intermediate valence ions; (2) The present invention also develops a method for causing the highest valence cation to directly react with the superstructure material, and promotes the transformation of the superstructure material into a structure containing the highest valence cation. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the cascade electroexchange reaction process; Figure 2 The first generation of Ag 7 O 8 NO 3 Superstructure materials to the second generation of hollow AgNiO 2 Schematic diagram of the conformal transformation process of superstructure materials and Ag 7 O 8 NO 3 and AgNiO 2 The crystal structure diagram of Figure 3 Ag 7 O 8 NO 3 Preparation and characterization of superstructure materials, among which, Figure 3 (A) is used for anodic electrodeposition of Ag 7 O 8 NO 3 Potential waveforms of superstructure materials; Figure 3 (B) shows the uniformly structured Ag selectively stripped from the electrode surface. 7 O 8 NO 3 Scanning electron microscope (SEM) images of superstructure materials; Figure 3 (C) in the graph is Ag 7 O 8 NO 3 X-ray diffraction (XRD) patterns of superstructure materials; Figure 4 AgNiO 2 SEM images and elemental mapping of superstructure materials; among them, Figure 4 (A) is AgNiO 2 SEM images of superstructure materials; Figure 4 (B) in the figure is the Ag element mapping; Figure 4 (C) in the figure is Ni element mapping; Figure 5 AgNiO 2 Energy dispersive X-ray spectra (EDS spectra), XRD spectra and X-ray photoelectron spectra (XPS spectra) of superstructure materials; among them, Figure 5 (A) is AgNiO 2 EDS spectra of superstructure materials; Figure 5 (B) is AgNiO 2 XRD spectra of superstructure materials; Figure 5 (C) is AgNiO 2 XPS spectra of superstructure materials; Figure 6 AgNiO 2 Superstructure Materials to AgCoO 2 Schematic diagram of conformal transformation of superstructure materials; Figure 7 The second generation AgNiO 2 Superstructure materials, third generation Ag(Ni,Co)O 2 Superstructure material cascade current displacement (CGD) reaction and complete galvanizing displacement (GD) reaction after AgCoO 2 SEM images and elemental mapping results of superstructure materials; among them, Figure 7 (A) is the second generation AgNiO 2 SEM images of superstructure materials; Figure 7 (B) is the second generation AgNiO 2 Ag element mapping results of superstructure materials (2μm); Figure 7 (C) is the second generation AgNiO 2 Ni element mapping results of superstructure materials (2μm); Figure 7 (D) is the second generation AgNiO 2 Ni element mapping results of superstructure materials (4μm); Figure 7 (E) is the third generation Ag(Ni,Co)O 2 SEM image of the CGD reaction of superstructure materials; Figure 7 (F) in the figure is the third generation Ag(Ni,Co)O 2 Ag element mapping results of the CGD reaction of superstructure materials (2μm); Figure 7(G) in the figure is the third generation Ag(Ni,Co)O 2 Ni element mapping results of the CGD reaction of superstructure materials (2μm); Figure 7 The (H) in the graph is the third generation Ag(Ni,Co)O 2 Co element mapping results of the CGD reaction of superstructure materials (2μm); Figure 7 (I) is AgCoO after complete GD reaction 2 SEM images of superstructure materials; Figure 7 (J) is AgCoO after complete GD reaction 2 Ag element mapping results of superstructure materials (2μm); Figure 7 (K) is the AgCoO after complete GD reaction 2 Co element mapping results of superstructure materials (2μm); Figure 7 (L) in the figure is AgCoO after complete GD reaction. 2 Co element mapping results of superstructure materials (3μm); Figure 8 AgCoO 2 XPS spectrum of the micro-torpedo; Fig. 9 AgNiO 2 and AgCoO 2 XRD spectra of superstructure materials; Fig.10 To monitor Co 3+ Ion pair Ni 3+ XPS spectra obtained from the displacement of ions; Fig.11 Schematic diagram of preparing the fourth, fifth and sixth generation superstructure materials by cascade electrical exchange reaction; wherein, Fig.11 (A) is a schematic diagram of the oxidation potentials of different cations referenced in Example 2; Fig.11 (B) is the fourth generation of hollow Ag(Ni, Co, Mn)O 2 Transmission electron microscopy (TEM) images and elemental mapping of superstructure materials; Fig.11 (C) is the fourth generation of hollow Ag(Ni, Co, Mn)O 2 SEM images and elemental mapping of superstructure materials; Fig.11 (D) in the figure is Ag(Ni,Co)O 2 and Ag(Ni,Co,Mn)O 2 EDS spectra of superstructure materials; Fig.11 (E) is the fourth generation Ag(Ni, Co, Mn, Fe)O 2 SEM images and elemental mapping of superstructure materials; Fig.11The (F) in the figure is the fifth generation Ag(Ni, Co, Mn, Cr)O 2 SEM images and elemental mapping of superstructure materials; Fig.11 (G) in the formula is Ag(Ni, Co, Mn, Fe)O 2 and Ag(Ni,Co,Mn,Cr)O 2 XPS spectra of superstructure materials; Fig.11 The (H) in the figure is the sixth generation Ag(Ni, Co, Mn, Cr, Fe)O in Example 2. 2 SEM images and elemental mapping of superstructure materials; Fig.12 Ag 7 O 8 NO 3 Superstructure materials converted into PbO 2 SEM images, EDS elemental images and XRD images; among them, Fig.12 (A) is PbO 2 SEM image and crystal structure; Fig.12 (B) is PbO 2 EDS element diagram; Fig.12 (C) in the equation is PbO 2 XRD pattern of Fig.13 Ag 7 O 8 NO 3 Superstructure materials converted to Fe 2 O 3 SEM images, EDS elemental images and XRD images; among them, Fig.13 (A) is Fe 2 O 3 SEM image and crystal structure; Fig.13 (B) is Fe 2 O 3 EDS element diagram; Fig.13 (C) in the formula is Fe 2 O 3 XRD pattern of Fig.14 Ag 7 O 8 NO 3 SEM image, EDS elemental image and XRD image of Ag converted from superstructure material; Fig.14 (A) is the SEM image and crystal structure of Ag; Fig.14 (B) is the EDS element map of Ag; Fig.14 (C) in the figure is the XRD pattern of Ag; Fig.15 Ag7 O 8 NO 3 Superstructure materials converted into Ag 2 SEM image, EDS elemental image and XRD image of S; Among them, Fig.15 (A) in the equation is Ag 2 SEM image and crystal structure of S; Fig.15 (B) in the figure is Ag 2 EDS elemental diagram of S; Fig.15 (C) in the graph is Ag 2 XRD pattern of S; Fig.16 Ag 7 O 8 NO 3 SEM images, EDS elemental images and XRD images of AgCl converted from superstructure materials; Fig.16 (A) is the SEM image and crystal structure of AgCl; Fig.16 (B) is the EDS element map of AgCl; Fig.16 (C) in the figure is the XRD pattern of AgCl; Fig.17 Ag 7 O 8 NO 3 SEM images, EDS elemental images and XRD images of AgI converted from superstructure materials; Fig.17 (A) is the SEM image and crystal structure of AgI; Fig.17 (B) is the EDS element map of AgI; Fig.17 (C) in the figure is the XRD pattern of AgI; Fig.18 For controllable movement of Ag(Fe,Co)O 2 Schematic diagram of the performance of magnetic superstructure materials; Fig.18 (A) is a schematic diagram of controlling the direction of the superstructure material without magnets and with moving magnets; Fig.18 (B) is a schematic diagram of controlling the direction of the superstructure material using magnets moving left and right respectively. DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with specific embodiments, application examples and drawings of the specification. The methods in the embodiments are conventional methods and conditions unless otherwise specified.

[0017] The present invention uses a material with a high oxidation potential as a template to undergo an ion exchange reaction with a metal salt solution with a low oxidation potential, thereby achieving not only component conversion, but also the preparation of a multi-element high entropy alloy. The driving force for the chemical conversion is the standard reduction potential difference of the material. The metal salt solution with a low oxidation potential contains metal cations (such as Mn) in a relatively low valence state or an intermediate valence state. 2+ Cr 3+ , Fe 2+ The superstructure material with high oxidation potential should contain cations with strong oxidation ability and mobility, and can oxidize most of the intermediate cations.

[0018] Ag 7 O 8 Nitrate superstructures tend to react with metal cations with low oxidation potentials. After reacting with metal cations with low oxidation potentials, they cannot react with metal cations with higher oxidation potentials than the former to form composite metal materials. 2+ The oxidation potential is 1.92 V, Ni 2+ 、Ni 3+ The oxidation potential of AgNiO is 1.977 V. 2 Superstructure materials immersed in Co 2+ Ionic solution, Ni 3+ Reduce, Co 3+ Gradually replace Co 2+ .AgNiO 2 and AgCoO 2 The crystal structure of Ni 3+ and Co 3+ The ionic radius of the AgNiO is similar, which enables it to maintain its shape during the process. 2 Superstructure materials gradually transform into the third generation Ag(Ni,Co)O 2 The superstructure material eventually transforms into AgCoO after the reaction is completed. 2 Using this principle, the present invention demonstrates that 7 O 8 Up to five cations are introduced into the microstructure of nitrate. 3+ 、Co 3+ , Mn 3+ Cr 6+ and Fe 3+ The order of introduction of Ag 7 O 8 Nitrate superstructure materials. Finally, the present invention realizes the sixth generation of Ag (Ni, Co, Mn, Cr, Fe) O 2 Fabrication of superstructure materials.

[0019] The materials prepared by the present invention have broad application prospects. For example, the hollow magnetic superstructures produced by this technology can be used as microcapsules to deliver drugs to the required locations in the human body. The silver superstructures have a wide range of applications as SERS substrates in the analytical and biomedical fields. 7 O 8 The morphology of the switching structures of the nitrate superstructure identifies different cations.

[0020] like Figure 1 As shown, it is a schematic diagram of the cascade electroexchange reaction process of the present invention; the process includes a strong oxidizing cation (such as Ag in the first step) 2+ 、Ag 3+ and M in the second step 3+ ) and the dissolution of intermediate ions (such as M in the first step 2+ and N in the second step 2+ ) oxidizing cations (such as M in the first step) 3+ and N in the second step 3+ ) precipitation.

[0021] Example 1: Metal Ni and Ag 7 O 8 NO 3 Superstructure materials are combined to form the first generation of superstructure materials.

[0022] Ag 7 O 8 The nitrate superstructure material is produced by three gradually decreasing potential waveforms, which is a columnar structure. The front and rear ends of the columnar structure have a pointed end and a thick end. The surface of the columnar structure has indentations distributed symmetrically in the center, and the whole structure is streamlined, such as Figure 3 Ag is shown 7 O 8 NO 3 Preparation and characterization of superstructured materials. By inserting electrodes into water, the structure of uniformly electrodeposited Ag 7 O 8 The nitrate superstructure material is selectively stripped from the electrode surface. High-valent silver ions can 2+ Oxidized to Ni 3 + (Oxidation potential: 1.977 V). 7 O 8 Nitrate superstructure materials introduce Ni 2+ In aqueous solution, Ag 3+ 、Ag 2+ From Ni 2+ Separate electrons to generate Ni 3+ In other words, with independent Ag 7 O 8The nitrate superstructure material is used as a positive electrode to form a conductive electrode with Ni 2+ Ions act as negative electrodes. High-valent silver ions gradually move from Ag 7 O 8 Diffusion within the nitrate core structure, Ni 3+ 、Ni 2+ The ions gradually attach to the Ag 7 O 8 The surface of nitrate superstructure material forms a growing AgNiO 2 Shell, such as Figure 2 As shown. Orthorhombic Ag 7 O 8 Nitrate and triangular crystal AgNiO 2 The crystallographic similarity of Ag 7 O 8 NO 3 、AgNiO 2 The lattice distortion between shells. Figure 4~Figure 5 AgNiO shown 2 SEM images, elemental mapping, and EDS, XRD, and XPS spectra of superstructure materials.

[0023] Example 2: In Ag 7 O 8 Up to five cations were introduced into the nitrate superstructure material.

[0024] According to the oxidation potential of the cation Fig.11 As shown in (A), according to Ni 3+ 、Co 3+ , Mn 3+ Cr 6+ and Fe 3+ The order of introduction of Ag 7 O 8 Nitrate superstructure materials. The first generation of Ag 7 O 8 The nitrate superstructure material is transformed into the second-generation superstructure material AgNiO 2 , the third generation superstructure material Ag(Ni,Co)O 2 , the fourth generation superstructure material Ag (Ni, Co, Mn) O 2 , the fifth generation Ag (Ni, Co, Mn, Cr) O 2 or Ag(Ni,Co,Mn,Fe)O 2 , and finally transformed into the sixth generation superstructure material Ag (Ni, Co, Mn, Cr, Fe) O 2 By using Ag(Ni,Co)O 2 Superstructure Materials and Mn 2+The fourth generation of hollow Ag(Ni,Co,Mn)O was obtained by cascading electrical exchange process between ions. 2 Superstructure materials, such as Fig.11 Similarly, the fifth generation of hollow Ag(Ni, Co, Mn, Fe)O 2 and Ag(Ni,Co,Mn,Cr)O 2 Superstructure materials, such as Fig.11 Finally, the present invention realizes the sixth generation Ag (Ni, Co, Mn, Cr, Fe) O 2 Fabrication of superstructure materials, such as Fig.11 As shown in (H) in the figure.

[0025] To prepare the third generation superstructure material Ag(Ni,Co)O 2 For example. Figure 6 AgNiO shown 2 Superstructure Materials to AgCoO 2 Schematic diagram of conformal transformation of superstructure materials, such as Figure 9~Figure 10 AgNiO shown 2 and AgCoO 2 XRD spectra of superstructure materials and monitoring of Co using XPS spectroscopy 3+ Ion pair Ni 3+ The result obtained by the displacement of ions; Figure 7 (A)~(L) show AgNiO 2 Superstructure materials, intermediate products Ag(Ni,Co)O 2 Superstructure materials, AgCoO 2 SEM image and element mapping results of the superstructure material. The open circuit voltage is used for detection. When the voltage is stable, it means that Co has completely replaced Ni to form AgCoO 2 In this embodiment, the AgNiO 2 Superstructure Materials to AgCoO 2 The complete transformation of superstructure materials. Therefore, Ag(Ni,Co)O 2 The superstructure material is the product when the voltage is not yet stable. In each ion exchange reaction, the progress of the ion exchange reaction is detected by the open circuit voltage, and the reactants are separated before the open circuit voltage value stabilizes (that is, the nth generation superstructure material obtained by the reaction is taken out of the solution).

[0026] Example 3: A method for causing the highest valence cation to directly react with a superstructure material.

[0027] The present invention develops a method for causing the highest valence cation to directly react with the superstructure material, and promotes the superstructure material to be transformed into a structure containing the highest valence cation. The intermediate valence cation solution is placed in a container, and Ag 7 O 8 The nitrate microstructures were placed in a solution of the highest cations in another container. A copper wire was used to connect the carbon rod immersed in the first container to the Ag- 7 O 8 The two containers are connected with a liquid bridge separated by a membrane that allows only nitrate ions to pass through. 2+ As the intermediate ion, Cu 2+ or Zn 2+ As its highest cation. Finally, Ag 7 O 8 The nitrate microstructure is transformed into copper oxide and zinc oxide microstructure.

[0028] More importantly, this setup can also introduce its highest valent cations into the microstructure. For example, Zn 2+ ions were successfully introduced into Ag(Ni,Co,Mn,Cr,Fe)O 2 In superstructure materials. For example, the elements of the intermediate valence ions can be replaced by reducing elements. 3+ Ag in aqueous solution 7 O 8 Applying a reduction potential to the nitrate superstructure material forms Fe 2 O 3 . Ag 7 O 8 NO 3 Superstructure materials can also be converted into metal oxides, metallic silver, silver sulfide and silver halide, such as Figure 12~Figure 17 PbO shown 2 , Fe 2 O 3 、Ag、Ag 2 Crystal structure, SEM image, EDS elemental map, and XRD map of S, AgCl, and AgI.

[0029] Application Example 1: Using hollow magnetic superstructures as microcapsules to deliver drugs in the human body.

[0030] The present invention further attempts to 7 O 8 Nitrate superstructure materials and Co 2+ and Fe 2+ The cascade electro-exchange reaction between Ag 7 O 8Nitrate superstructure material converted into hollow Ag(Co,Fe)O 2 Magnetic superstructure materials. Hollow Ag(Co,Fe)O 2 Magnetic superstructure materials respond to magnetic fields. Magnetic superstructure materials can move quickly under the attraction of magnets and can instantly adjust the direction of movement. Fig.18 As shown in (A) to (B), from Ag(Fe, Co)O 2 The superstructure material is pointed from I to II, III and V, and it can be seen that Ag(Fe, Co)O 2 Magnetic metastructures can move in response to magnets.

[0031] These hollow magnetic superstructures have potential applications as microcapsules to deliver drugs where needed in the human body.

[0032] Application Example 2: Porous silver superstructures are widely used as SERS substrates in analytical and biomedical fields.

[0033] Electrochemical reduction of Ag 7 O 8 Nitrate-converted nanoporous silver superstructures can be used as surface enhanced Raman scattering (SERS) sensing substrates. The size of the nanopores in the silver superstructures can be controlled by the reduction potential. The Ag superstructures prepared under 3V electroreduction conditions showed outstanding SERS performance. These nanopores can significantly enhance the electromagnetic field, showing as SERS hotspots. Strong SERS peaks were observed for crystal violet (CV) molecules from their aqueous solutions at concentrations ranging from 10 µm to 100.0 fm. These porous silver superstructures have a wide range of applications as SERS substrates in analytical and biomedical fields.

[0034] Application Example 3: Based on Ag 7 O 8 The morphology of the switching structures of nitrate superstructures recognizes different cations.

[0035] Ag 7 O 8 Nitrate superstructures can be used to detect intermediate ions. After 24 hours, a drop of Ag mixed 7 O 8 NO 3 The liquid dries on the smooth surface to form nanorods and nanoparticles. In contrast, even in the presence of 1µm Mn 2+ 、Co 2+ or Ni 2 + , Ag 7 O 8 The conversion structure morphology of nitrate superstructure materials also undergoes significant changes.7 O 8 Nitrate superstructures switch the morphology of their structures to recognize different cations.

[0036] It should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Without making creative work, any modification, equivalent replacement, improvement, etc., shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high entropy alloy using cascade electrical exchange technology, characterized in that: The following steps are involved: Using (Ag7O8)X superstructure material as a template, ion exchange reactions are sequentially carried out with various metal salt solutions; in each ion exchange reaction, the progress of the ion exchange reaction is detected by open circuit voltage, and the reactants are separated before the open circuit voltage value stabilizes, thereby preparing a multi-component high entropy alloy hollow superstructure material; The oxidation potential of the metal cations in the plurality of metal salt solutions is lower than the oxidation potential of the silver ions in the (Ag7O8)X superstructure material, and the oxidation potential gradually decreases in the order in which the (Ag7O8)X superstructure material is introduced; the X anion is selected from NO3 - , HSO4 - , ClO4 - , F - , BF4 - One or more of .

2. The method according to claim 1, characterized in that The concentration of the metal salt solution is greater than 50 mmol / L.

3. The method according to claim 1, characterized in that The (Ag7O8)X superstructure material is prepared by the following method: a three-electrode system is used, a deionized water solution containing a silver ion compound and H3BO3 is used as an electrolyte, and a step-by-step decreasing voltage mode or a multiple step-by-step decreasing voltage mode is used to electro-deposit the (Ag7O8)X superstructure material on a working electrode; wherein the voltage of the electro-deposition is greater than or equal to 1.5 V, and the silver ion compound is one or more of AgNO3, Ag2SO4, AgClO4, AgF, and AgBF4.

4. The method according to claim 1, characterized in that: Using (Ag7O8)X superstructure material as a template, ion exchange reactions are sequentially carried out with a variety of metal salt solutions, specifically: using (Ag7O8)X superstructure material as a conductive electrode, using metal cation solution as an electrolyte, and carbon rods as counter electrodes; high-valent silver ions gradually diffuse from the (Ag7O8)X superstructure material from the inside to the outside, and metal cations gradually adhere to the surface of the (Ag7O8)X superstructure material to form a growing AgYO2 shell, thereby obtaining a second-generation hollow metal oxide material AgYO2, wherein Y is a metal element in the metal cation; using the second-generation hollow metal oxide material AgYO2 as a template, repeating the above steps, reacting with metal cations with an oxidation potential lower than Y, thereby obtaining a multi-generation and multi-component high-entropy alloy hollow superstructure material.

5. The method according to claim 4, characterized in that Also includes: The highest valence cation is introduced into the (Ag7O8)X superstructure material or the nth generation multi-component high entropy alloy hollow superstructure material, specifically, the intermediate valence cation solution is placed in a first container, a carbon rod is inserted, the highest valence cation solution to be introduced is placed in a second container, a gold electrode covered by the (Ag7O8)X superstructure material or the nth generation multi-component high entropy alloy hollow superstructure material is inserted, the gold electrode is connected to the carbon rod by a copper wire, the first container and the second container are connected by a liquid bridge, an ion exchange membrane is arranged in the liquid bridge, and only X anions are allowed to pass; wherein the oxidation potential of the intermediate valence cation is higher than that of the highest valence cation.

6. A multi-component hollow superstructure material prepared by the method according to any one of claims 1 to 5.

7. Use of the multi-component hollow superstructure material according to claim 6 in preparing microcapsules, characterized in that: Adopt Co 2+ and Fe 2+ A metal salt solution is prepared to obtain Ag(Co, Fe)O2 magnetic superstructure material, and the microcapsule is used to deliver drugs to target locations in the human body.

8. Use of the multi-component hollow superstructure material according to claim 6 in preparing a SERS substrate.

Citation Information

Patent Citations

  • Electrode materials for magnesium batteries

    CN103155235A

  • Manufacturing method for multi-stage three-dimensional micro structure

    CN110117802A

  • High-entropy single-crystal metal oxide with cation disordered rock salt structure and preparation method and application thereof

    CN113584591A

  • Ordered localized nanostructure capable of realizing enrichment detection as well as preparation method and application of ordered localized nanostructure

    CN118169097A

  • Method for purifying soil containing organic pollutants

    KR1020240080396A